Business in practice - analysis of an automotive company´s transformation and reflection on personal journey - Funke, Amira Luise Clara (2023)
This thesis examines the development of a fictional company within the electric vehicle industry as part of a business simulation developed by IndustryMasters®. The industry is disrupted by technological advancement and a growing environmental consciousness. The journey of the company provides valuable insights for the automotive sector and demonstrates the importance of robust and aligned strategies in transforming a business. Specifically, the strategy, innovation, and marketing functions are examined. This paper also provides a personal reflection on the author's role within their team in the simulation and highlights the importance of confidence, communication, and a quick resolution of conflicts.